SELECTIVITY OF THE HERBICIDE CHLORIMURON ETHYL ON YOUNG COFFEE PLANTS - Castanheira, Dalyse Toledo; Voltolini, Giovani Belutti; Alecrim, Ademilson de Oliveira; Rezende, Tiago Teruel; Netto, Pedro Menicucci; Silva, Larissa Cocato da; Guimarães, Rubens José (Coffee Science - ISSN 1984-3909, 2019)
The great interference of weeds in coffee plants, due to competition for water, light and nutrients, makes their control essential. Among these control methods, the chemical stands out, due to its high efficiency and low cost. However, as a function of application failures, phytotoxicity is frequent in coffee plants due to herbicide drift. Aiming to search for active ingredients selective to coffee, the objective of this study was to evaluate the selectivity of the active ingredient Chlorimuron ethyl in coffee seedlings, and its effects on plant morphology, anatomy and physiology. The experiment was carried out in a greenhouse with ‘Topázio MG 1190’ coffee plants (Coffea arabica L.), grown in 11-L pots. The statistical design was in randomized blocks, with four replications and four herbicide doses. Each plot consisted of three plants. The treatments were: 0%; 50%; 100% and 200% of the recommended commercial dose of the herbicide Chlorimuron ethyl. Evaluations were performed at 120 days after treatment application. Morphological, physiological and anatomical characteristics were evaluated, besides possible phytotoxicity symptoms inherent to herbicide application. The herbicide Chlorimuron ethyl caused phytotoxicity symptoms in coffee seedlings, evidenced from the leaflet dose, through leaf deformation and cracking, with growth losses not exceeding 10%, but without damage to plant physiology and anatomy.